Understanding Blood-Flow Dynamics: New Challenges for Visualization. - van Pelt, Roy; Vilanova, Anna (Computer (00189162), 2013)
Modern simulation and imaging techniques are providing intricate blood-flow velocity data, the analysis of which can lead to new insights into how blood flow relates to the development of cardiovascular disease. Rapidly interpreting this complex data requires novel comprehensive visual representations.